Asia-Pacific contemporary finance and development - Barnett, William A.; Sergi, Bruno S. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Asia-Pacific Contemporary Finance and Development collects a well-informed range of fourteen chapters, investigating banking, finance, production, and consumer sectors that are vital shares of modern economies and definitive drivers of growth in the Asia-Pacific economies. The chapters, authored by internationally renowned and experienced academics, showcase the most updated economic and entrepreneurial dynamism in the Asia-Pacific, a large and thriving region that is recognized as a driving force of innovation and economic growth worldwide. From the TPP and the U.S., to short-term cross-currency basis swap and Japanese government bond markets, and from volatility and risk-taking firms and corporate diversification strategy and the political effects of the Corporate Social Responsibility, to consumption propensity and entrepreneurship, this volume of The International Symposia in Economic Theory and Econometrics explores and investigates contemporary challenges and issues facing the Asia-Pacific economies. For researchers and students of economics and finance, this volume is a fascinating exploration of emerging topics in one the fastest growing economies in the world.
Prelims -- Asia Pacific, Trans-Pacific partnership, and the United States: the network perspective -- Short-term cross-currency basis swap and Japanese government bond markets under non-traditional monetary policy -- The impacts of working capital policy on firms' performances: an empirical study on thai listed companies in production sector -- Local amenities and geographic disparity in population and industry distribution in Korea -- Modeling of critical success factors of Thai retailers: interpretive structural modeling approach -- Strategic risk management in the Chinese property and casualty insurance industry -- Economic consequences of insider-ownership: an emerging market perspective -- Central Asia and China: financial development through cooperation with Russia -- The impact of risk-taking on firm volatility -- What determines Sukuk issuance type in Indonesia? -- Does the method of corporate diversification matter to firm's performance? -- Corporate political activity and financial performance: a corporate social responsibility perspective -- Consumption propensity and entrepreneurship: evidence from China -- Explaining systemic risk in Latin American banking industry over 20022015 -- Index.
Includes index.
Print version record.
Keywords: Finance -- Pacific Area; Economic development -- Pacific Area; Business & Economics -- Economics -- General; Economics